PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI MIA SMA NEGERI 1 KOTO XI TARUSAN - Syofia Ulva (Departemen Matematika, 2020)
Understanding mathematical concepts of students in class XI MIA SMA 1 Koto XI Tarusan is still low, this shows via the mathematical results of the tested concepts. The solution to this problem is found in Two Stay Two Stray cooperative learning model (TSTS). The study aims to describe the understanding of mathematical concepts of students who learn using TSTS better than students who use conventional learning. The study describes the development of students mathematical understanding of concepts during the implementation of TSTS in class XI MIA SMA 1 Koto XI Tarusan. This type of quasi-experimental research uses the non-equivalent posttest-only control group design. Research data were collected through quizzes and tests of students' understanding of mathematical concept skills. Data analysis using t-test. The result analysis state that the development of understanding mathematical concepts by students has increased while using TSTS. Based on the results of hypothesis testing, it appears that understanding mathematical concepts of students who use TSTS is better than students who use conventional learning. Keywords —Two Stay Two Stray, Mathematics learning, Mathematical concepts